Rancang Bangun Sistem Informasi Administrasi Lembaga Sertifikasi Profesi (LSP) Berbasis Web - Nur Alamsyah; M Muflih; Muharir; Muhammad Edya Rosadi (SMARTICS Journal, 2020)
Professional Certification Authority (LSP) is an implementing agency for certification activities that are licensed by the Indonesian Professional Certification Authority (BNSP). Based on BNSP, in August 2019 there were 28,135 assessors, 120 master assessors, 13,559 competency test sites. In terms of the type of certification, there are three types of LSP, namely LSP P1, which amounts to 1,174, LSP P2 totalling 74, and LSP P3 totalling 280. LSP FTI UNISKA Banjarmasin is one of 56 LSP types P1 Universities spread throughout Indonesia. At present, the administration at LSP FTI UNISKA Banjarmasin, starting from registering participants to conducting competency tests, remains still fulfilled manually. Hence, administrators and directors often feel problems in taking out the certification process. Through this research, a web-based LSP administration application designed by collecting data using observation, interviews, and documentation studies, then information systems designed using the waterfall method. From the results of the research succeeded in designing an information system that can help the data administration process of competency test participants, scheduling, administration as well as making the competency test results report.